Kajian Tentang Peran Emotional Branding dalam Kebangkitan UMKM F&B Lokal Pasca Gerakan BDS: - - Rafi Rahman Fauzi; Wiwi Isnaini (Serat Rupa: Journal of Design, 2026)
The boycott of several global brands after 2023 has triggered changes in consumption patterns, particularly among Generation Z, known as digital-native consumers. This study aims to analyze how Generation Z responded to the boycott and its impact on consumption preferences for global versus local brands in the food and beverage (F&B) sector. Furthermore, this study investigates Generation Z's response to a visual campaign themed "local products" as an element of post-boycott brand communication. The method used was quantitative, with a survey involving 102 Generation Z respondents, supplemented by qualitative data from their open-ended responses. The results indicate that most respondents adjusted their consumption behavior in response to the boycott issue, accompanied by increased exploration and consumption of local brands. Local brands were seen as a viable alternative based on initial experience, product quality, and affordability, although the extent of loyalty remains situational. Other findings indicate that Generation Z responds positively to locally themed visual campaigns, but this interest is acoustic and influenced by visual quality, conceptual clarity, and the relevance of the presented identity. Local visual campaigns have the potential to strengthen consumer emotional bonds if they can be translated authentically and contextually through consistent and distinctive visual communication design.